ASEAN's economic security and regional economic cooperation: past, present, and future - Lee, Su-Hyun (2022)
Since the end of the Cold War, ASEAN has continuously increased its level of integration into the global economy to enhance regional economic prosperity and stability. Given the conceptual fluidity of economic security in international relations, however, ASEAN's firm commitment to promoting positive synergies between economic and security interests warrants further attention. In this vein, this article examines the evolving nature of ASEAN's economic security with a focus on regional economic initiatives, including trade agreements and the ASEAN Economic Community. The article suggests that ASEAN can maximize its potential for economic security when it increases the credibility of its commitment to regional economic cooperation and integration. To do so, ASEAN should more effectively address the issues of weak institutional capabilities and domestic political conflicts over regional economic governance. It should also proactively respond to unexpected challenges from external factors, such as US–China rivalry and the COVID-19 pandemic.